Pemikiran Ibn Khaldun tentang Pendidikan Islam - Hasby, A.Kahar Muzakar (TAJDID, 2017)
This article tries to explore Ibnu Khaldun's concept of education in many perspectives. His most important view on education is that education plays the most urgent roles in developing human civilization. According to Ibnu Khaldun, education should involve two aspects, material and spiritual. This view was based on the argumentation that human need is a combination of the two aspects. That's why, according to his opinion, the purpose of education should meet both potencies simultaneously. However, regarding that spiritual factor mostly affect the human life, furthermore, he says that spiritual education should be prioritized.